Multifaceted chikungunya infection in infants - A case series (Indian Journal of Case Reports, 2020)
Chikungunya is an epidemic viral disease. It is known to cause explosive outbreaks after disappearing for several years. The clinical manifestations among infants are entirely different as compared to adults and older children. It can go undiagnosed in the garb of sepsis unless strong clinical suspicion is present. We report a series of infants presenting with neurological, circulatory, and cutaneous manifestations.